Evaluative Analysis of Basic Education Facilities and Infrastructure Management: Case Study at SDN Gambiran 01 Jember - Robith Fadyan Asfa; Rizqi Hidayatul Lael; Siti Maryamah; Siti Makrifatus Sholehah; Rofiq Hidayat (CV. Yazri Aksara Nusantara, 2025)
Purpose - This study evaluates the management of facilities and infrastructure, a crucial component for learning quality in public primary schools. Persistent issues like inadequate facilities and weak maintenance prompted an in-depth examination of facility management at SDN Gambiran 01 Jember. The study aims to assess how facilities are planned, implemented, and evaluated to meet institutional needs.Design/methods/approach – A qualitative case study approach was used. Data were collected through in-depth interviews, field observations, and document analysis, then analyzed using the Miles and Huberman interactive model. Participants, including the school principal, teachers, and administrative staff involved in facility management, were purposively selected.Findings – Facility planning and procurement are conducted in a participatory, needs-based manner, aligning with regulations. However, utilization and maintenance face challenges due to budget limitations, lack of technical personnel, and limited technology use. A culture of cooperation and adaptive leadership emerged as key supporting factors.Research implications/limitations – The study is limited by its focus on a single institution and reliance on qualitative data. Implications highlight the need for targeted technical training for elementary school staff and developing data-driven evaluation systems to inform long-term educational policy.